Exposure to e-cigarette vapor extract induces vocal fold epithelial injury and triggers intense mucosal remodeling - Vlasta Lungova; Kristy Wendt; Susan L. Thibeault (The Company of Biologists, 2022)
Vaping has been reported to cause acute epiglottitis, a life-threatening airway obstruction induced by direct epithelial injury and subsequent inflammatory reaction. Here, we show that we were able to recapitulate this phenomenon in vitro. Exposure of human engineered vocal fold (VF) mucosae to 0.5% and 5% electronic cigarette (e-cigarette) vapor extract (ECVE) for 1 week induced cellular damage of luminal cells, disrupting homeostasis and innate immune responses. Epithelial erosion was likely caused by accumulation of solvents and lipid particles in the cytosol and intercellular spaces, which altered lipid metabolism and plasma membrane properties. Next, we investigated how the mucosal cells responded to the epithelial damage. We withdrew the ECVE from the experimental system and allowed VF mucosae to regenerate for 1, 3 and 7 days, which triggered intense epithelial remodeling. The epithelial changes included expansion of P63 (TP63)-positive basal cells and cytokeratin 14 (KRT14) and laminin subunit α-5 (LAMA5) deposition, which might lead to local basal cell hyperplasia, hyperkeratinization and basement membrane thickening. In summary, vaping presents a threat to VF mucosal health and airway protection, thereby raising further concerns over the safety of e-cigarette use. This article has an associated First Person interview with the first author of the paper.